Intrinsically anisotropic 1D NbTe4 for self-powered polarization-sensitive photodetection - Huahu Luo; Fafa Wu; Chaowei He; Wanfu Shen; Chunguang Hu; Weina Zhao; Peng Yu; Guowei Yang (NPG Asia Materials)
Abstract Polarization-sensitive photodetection enhances scene information capture, crucial for modern optoelectronic devices. One-dimensional (1D) materials with intrinsic anisotropy, capable of directly sensing polarized light, are promising for such photodetectors. NbTe4, a quasi-1D transition metal tetra-chalcogenide, offers significant benefits for polarization-sensitive photodetection due to its structural anisotropy. Nonetheless, to date, the anisotropic properties of 1D NbTe4 have not been reported. Herein, NbTe4 nanobelts were synthesized via mechanical exfoliation from needle-like bulk crystals, and their anisotropic and optoelectronic properties were comprehensively studied. Angle-resolved polarized Raman spectroscopy, in conjunction with azimuth-dependent reflectance difference microscopy, confirmed that 1D NbTe₄ exhibits intrinsic structural and in-plane optical anisotropy. The 1D NbTe4 device demonstrated characteristic anisotropic photodetection behavior, achieving dichroic ratios of 1.16 at 671 nm and 1.25 at 1064 nm. Meanwhile, the device exhibits a pronounced photothermoelectric effect, conferring a broad spectral photoresponse ranging from visible to near-infrared wavelengths (532-1064 nm), with a rapid response time of 158 ms. This study demonstrates that NbTe4 inherently possesses in-plane anisotropy, making it a promising candidate for polarization-sensitive photodetection applications.